The Malay world relations with The Ottoman Caliphate with special reference to Pan-Islamism in Malaya - Mansor Majdin, Mohamad Firdaus (UMT Press, 2022)
The Muslims in Malaya, namely the three core segments of the community, the Malays, the Arabs and the Indians, followed the events relating to the Ottoman Caliphate with keen interests. This has been reflected in the Malay press which covered news pertaining to the Caliphate extensively especially on matters concerning the wars with other Western powers and her Balkans territories. There was also news on its Sultan and the military capability of the Caliphate vis-à-vis the growing strength of the Western powers. This has demonstrated that the Muslims at that point of time had shown their interests and concerns over the well-being of the Caliphate. Nevertheless, though the Muslims felt attached to events relating to the Caliphate, their degree of interest and concern was varied. Using a content-textual analysis, the study demonstrates that the general Malay-Muslims had shown little interest and attachment towards the Caliphate on one hand and realized also that the British colonial government had used 'the Malay court factor', for instance, in the eve of First World War, to curtail Muslims’ support for Turkey at one hand and the Malay Sultans on the other. This however, not by all means, tried to marginalize the involvement of certain segment of Malay Muslims in showing their support towards the Caliphate such as in the case of the gathering of the Malay-Muslims in the Madrasah Ihsaniah and the fund-raising campaign led by one of Perak royalty where its donation was to be used subsequently for the Ottoman war efforts.